Efektivitas Pijat Oksitosin Terhadap Kecukupan Asi Pada Bayi di TPMB Wilayah Kerja Puskesmas Talang Tinggi Kabupaten Seluma - Herlinda, Herlinda; Elvina, Ade; Widyaningsih, Sari; Carlita, Dea (Universitas Malahayati, 2025)
ABSTRACT Oxytocin massage can stimulate the let down reflex and help release the hormone oxytocin, so that the mother gets comfort which ensures breast milk production can be maintained. This study aims to determine the effectiveness of oxytocin massage on the adequacy of breast milk for babies in the TPMB working area of the Talang Tinggi Community Health Center in 2024. The population in this study were all mothers who gave birth in the TPMB working area of the Talang Tinggi Public Health Center, Seluma Regency in March-April 2024, totaling 32 people. The sampling method in this study was total sampling. Data collection uses primary data, processed univariately and bivariately. The results of the univariate analysis before the oxytocin massage was carried out, almost all 22 (69%) of them expressed insufficient breast milk. After being given oxytocin massage, the majority of 25 (78%) babies had enough breast milk. The results of the bivariate analysis show the effectiveness of oxytocin massage on the adequacy of breast milk for babies in the TPMB Working Area of the Talang Tinggi Community Health Center, Seluma Regency in 2024. It is hoped that midwives will be able to create an education program for the community regarding how to increase the adequacy of breast milk for babies by doing oxytocin massage. Keywords: Oxytocin Massage, Postpartum Mother, Adequate Breast Milk ABSTRAK Pijat oksitosin dapat merangsang pada reflex let down dan membantu pelepasan hormon oksitosin, sehingga ibu mendapatkan kenyamanan yang membuat produksi ASI dapat dipertahankan. Penelitian ini bertujuan untuk mengetahui efektivitas pijat oksitosin terhadap kecukupan ASI pada bayi di TPMB wilayah kerja puskesmas Talang Tinggi tahun 2024. Populasi dalam penelitian ini adalah semua ibu yang melahirkan di TPMB wilayah Kerja Puskesmas Talang Tinggi kabupaten Seluma pada bulan Maret-April 2024 berjumlah 32 orang metode pengambilan sampel dalam penelitian ini adalah total sampling. Pengumpulan data menggunakan data primer, diolah secara univariat dan bivariate. Hasil analisis univariat sebelum dilakukan pijat oksitosin hampir seluruh 22(69%) pengeluaran ASI tidak cukup. Sesudah diberikan pijat oksitosin sebagian besar 25 (78%) kecukupan ASI pada bayi cukup. Hasil analisa bivariate ada efektivitas pijat oksitosin terhadap kecukupan ASI pada bayi di TPMB Wilayah Kerja Puskesmas Talang Tinggi Kabupaten Seluma tahun 2024. Diharapkan bidan untuk dapat untuk membuat program penyuluhan kepada masyarakat mengenai cara peningkatkan kecukupan ASI pada bayi dengan cara melakukan pijat oksitosin. Kata Kunci: Pijat Oksitosin, Ibu Nifas, Kecukupan ASI